Microstructural Evolution during Thermal Exposure of G115 Steel and Its Influence on Mechanical Properties. (23rd April 2022) - Ma, Shaohai; Yan, Kai; Che, Chang; Yang, Xisheng; Qian, Gong
Abstract : Microstructural evolution and mechanical property degradation of the newly developed G115 steel during thermal exposure are highly important for the safe power plant operation. In this paper, the microstructural stability and strength as well as impact toughness were investigated after aging at 650°C and 700°C up to 5000 h. It was found that when aged at 650°C in the G115 steel, the size of M23 C6 carbides and the width of martensitic laths had little change even increasing aging time up to 5000 h. Both the room-temperature and high-temperature strengths remained stable after aging for 5000 h. In comparison, after aging at 700°C, high-density Laves phases precipitated accompanied by coarsening with increasing aging time. The majority of martensitic lath structure was replaced by sub-grains and the strength decreased linearly. Most importantly, the impact toughness of G115 steel aged at both 650°C and 700°C decreased sharply and embrittlement occurred rapidly in the initial aging period. The evidence provided by fracture morphologies proved that Laves phase was the culprit of decreasing the impact toughness.